2018
DOI: 10.2174/1573402114666180423110658
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Vascular Evaluation: From Laboratory Experiments to Point-of-Care Patient (Experimental Approach)

Abstract: This paper illustrates the evolution of our knowledge of arterial mechanics from our initial research works up to the present time. Several techniques focusing on this topic in terms of our experience are discussed. An interdisciplinary team composed by different institutions from Argentina, Uruguay, France and Spain was created to conduct research, to train human resources and to fulfill the inevitable social role of gaining access to technological innovation to improve public health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 47 publications
0
2
0
1
Order By: Relevance
“…Previously, CVD risk was only assessed by the presence of CVD risk factors such as old age, hypertension, obesity, high cholesterol and low HDL [ 45 ]. There is some experimental evidence against the use of only CVD risk factors in identifying individuals at high risk from the normal ones [ 46 , 47 ]. It was reported that traditional CVD risk factors alone explain only 60–65% of the CVD risk, and the presence of one or more risk factors is common even among individuals who may not develop a clinical disease [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, CVD risk was only assessed by the presence of CVD risk factors such as old age, hypertension, obesity, high cholesterol and low HDL [ 45 ]. There is some experimental evidence against the use of only CVD risk factors in identifying individuals at high risk from the normal ones [ 46 , 47 ]. It was reported that traditional CVD risk factors alone explain only 60–65% of the CVD risk, and the presence of one or more risk factors is common even among individuals who may not develop a clinical disease [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…In order to validate the proposed methodology and open new lines of research, in vivo P-D measurements such as those detailed in [ 29 , 30 ] should be performed. It is noteworthy that the virtual subjects considered in this study were simulated assuming a healthy condition.…”
Section: Discussionmentioning
confidence: 99%
“…La PA puede analizarse como el resultado de la combinación de una onda de presión anterógrada (que proviene del corazón) y una onda retrógrada (que vuelve de sitios específicos caracterizados por coeficientes de reflexión específicos). Ambas ondas se propagan (en direcciones opuestas) a una velocidad de fase dependiente de la rigidez arterial, definida como -Velocidad de la Onda de Pulso Arterial‖ (VOP) [3]. Debe tenerse en consideración que las alteraciones en las grandes arterias constituyen un importante factor de morbilidad y mortalidad cardiovascular.…”
Section: Introductionunclassified